Classification of European Union Countries with Regard to The Security Level of ICT Services Use in Enterprises - Iwona BĄK; Katarzyna WAWRZYNIAK; Maciej OESTERREICH (Communications of International Proceedings, 2021)
The study aims to analyze the degree of differentiation in the level of security of ICT use in enterprises operating in the European Union. A taxonomic measure of development based on the median Weber vector was used to classify the member states according to the studied phenomenon. Indicators related to the safe use of information and communication technologies (ICT) were adopted as diagnostic features. Typological groups of countries with a similar situation in terms of security of ICT use were distinguished using the three median method. Additionally, the obtained values of synthetic variables were compared with selected macroeconomic categories. The conducted research shows that the level of security of using ICT in enterprises operating in the EU is varied and depends on the wealth of countries, the structure of their economy, and the level of education of the population.
Keywords: ICT; Security; Enterprises; Multidimensional Statistical Analysis